Proteasomal degradation induced by DPP9-mediated processing competes with mitochondrial protein import - Finger, Yannik; Habich, Markus; Gerlich, Sarah; Urbanczyk, Sophia; van de Logt, Erik; Koch, Julian; Schu, Laura; Lapacz, Kim Jasmin; Ali, Muna; Petrungaro, Carmelina; Salscheider, Silja Lucia; Pichlo, Christian; et al. (EMBO Journal, 2020)
Plasticity of the proteome is critical to adapt to varying conditions. Control of mitochondrial protein import contributes to this plasticity. Here, we identified a pathway that regulates mitochondrial protein import by regulated N-terminal processing. We demonstrate that dipeptidyl peptidases 8/9 (DPP8/9) mediate the N-terminal processing of adenylate kinase 2 (AK2) en route to mitochondria. We show that AK2 is a substrate of the mitochondrial disulfide relay, thus lacking an N-terminal mitochondrial targeting sequence and undergoing comparatively slow import. DPP9-mediated processing of AK2 induces its rapid proteasomal degradation and prevents cytosolic accumulation of enzymatically active AK2. Besides AK2, we identify more than 100 mitochondrial proteins with putative DPP8/9 recognition sites and demonstrate that DPP8/9 influence the cellular levels of a number of these proteins. Collectively, we provide in this study a conceptual framework on how regulated cytosolic processing controls levels of mitochondrial proteins as well as their dual localization to mitochondria and other compartments.
CRIS-Team Scopus Importer:2020-08-28
Keywords: adenylate kinase 2; dipeptidyl peptidase 9; MIA40; mitochondrial protein import; quality control